Glocalizing the Micro-Enterprise: The Role of Region-of-Origin and Code-Switching in MSME Export Strategies - Gustiawan, Wahyu Dede; Sudarmiatin; Pratikto, Heri (Universitas Kadiri, 2026)
Conventional internationalization theories often fail to represent the dynamics of the expansion of Micro, Small, and Medium Enterprises (MSMEs) in developing countries because they ignore the disruption of digitalization and the urgency of local cultural adaptation. This research aims to explore and deconstruct the strategic mechanism of MSMEs in extracting regional identity (Region-of-Origin) and integrating it into global brand communication in the digital platform ecosystem. This study adopts a qualitative design through a multiple case study approach. Primary data was collected through in-depth semi-structured interviews with strategic decision-makers in five leading MSME exporters in Kediri City, East Java, including the craft and agro-industry sectors. Thematic analysis is applied systematically to reduce data and map patterns of cross-cultural communication strategies. The data analysis identified three main strategic findings: (1) the commodification of local sociocultural heritage into digital visual narratives functions as an authenticity signaling instrument that allows MSMEs to set premium prices; (2) dynamic interaction through live commerce platforms facilitates the formation of parasocial relationships that radically reduce psychological distance and trigger impulse purchase decisions from foreign buyers; and (3) the application of hybrid communication tactics through linguistic code-switching acting as a clever socio-symbolic mechanism in bridging the prestige of the global market with cultural authenticity. This study contributes an original contribution to the international business literature by constructing an integrative framework that synergizes the principles of Network Theory, dynamic capability agility, and cultural localization in the cyber landscape. This study emphatically shifts the focus of the literature from the macro effects of Country-of-Origin to the micro-power of Region-of-Origin, while offering an empirical and managerial blueprint for MSMEs in developing countries to capitalize on the narrative of regionality as a highly competitive intangible asset.